Clinical Characteristics and Outcome of Readmitted Adult Patients With Acute COVID-19 Infection Within 30 Days of Their Hospital Discharge - Nawaf Abdulaziz Alobaid; Ali Abdulrahman Alsalamah; Mohmmed Ibrahim Mugren; Abdulaziz Mohammed Alhwairini; Mohammed Ali Alzahrani; Nawaf M. Alzahrani; Omar Baharoon; Jinan Shamou; Eiman Alsafi; Salim Baharoon (Canadian Journal of Infectious Diseases and Medical Microbiology)
Conclusion: The readmission rate after acute COVID-19 infection was 5.7%, aligning with rates reported internationally. The most frequent causes of readmission were persistent COVID-19 pneumonia, renal impairment, and urinary tract infections, while secondary bacterial pneumonia at readmission was rare. Readmission was associated with increased rates of ICU admission and the need for mechanical ventilation. The use of NEWS at discharge may serve as a useful criterion for determining readiness for discharge. Future follow-up of this cohort of patients will determine chronic long-term respiratory complications.